Pressure mapping bandage prototype: Development and testing - Al Khaburi, Jawad; Dehghani-Sanij, Abbas A.; Nelson, E. Andrea; Hutchinson, Jerry (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/